Transforming the Millennium Development Goals (MDGs) to Social Development Goals (SDGs) in Manufacturing Companies - Purnamasari, Pupung; Frendika, Rusman; Dzikron, Muhamad (KnE Social Sciences, 2023)
This study aims to analyze the transformation of the millennium development goals (MDGs) into social development goals (SDGs) in manufacturing companies in Banten Province. The specific objectives of this study are to analyze the relationship: 1) Environmental transformation with sustainable practices (E-MDGs); 2) Social transformation with sustainable practices (S-MDGs); 3) Transformation of governance with sustainable practices (G-MDGs); 4) Overall ESG transformation with existing manufacturing company sustainability practices in Banten Province and provides a framework for understanding sustainable transformation processes (MDGs-SDGs). The data analysis technique used in this research is descriptive and inferential non-parametric statistics using SPSS v 25 and SEM-AMOS v25 analysis tools. The SDGs analysis was carried out using 14 criteria, and the MDGs 8 criteria. Primary data was obtained by interviewing and distributing questionnaires to 103 respondents via a Google form. The results of this study show that manufacturing companies in Banten Province have already implemented sustainability programs, most of which are still in line with the MDGs. Keywords: transformation, environment, social, governance, sustainability